2017
DOI: 10.1590/s1980-6574201700010004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of constant practice in transfer tests

Abstract: -Background:There is a consensus that repetition observed in constant practice produces minimal benefits to the transfer of learning. Objective: The purpose of this study was to investigate in 3 experiments the effects of constant practice in transfer contexts. Methodology: Participants were asked during acquisition phase, in all experiments, to press four keys sequentially with different requirements of absolute timing in a same relative timing structure. In the transfer tests, they were tested in a novel abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…This proposition was based on behavioral findings, which indicated that constant practice benefits learning of the relative timing of the movement, and random practice benefits the learning of the absolute timing. 4,25,26 The results found by Bicalho et al 18 confirmed partially the hypothesis. As expected, random practice showed a higher amount of KR and goal information gathered from the absolute dimension than constant practice.…”
Section: Practice Organization: Could Perceptual Processes Be Affected?mentioning
confidence: 52%
See 1 more Smart Citation
“…This proposition was based on behavioral findings, which indicated that constant practice benefits learning of the relative timing of the movement, and random practice benefits the learning of the absolute timing. 4,25,26 The results found by Bicalho et al 18 confirmed partially the hypothesis. As expected, random practice showed a higher amount of KR and goal information gathered from the absolute dimension than constant practice.…”
Section: Practice Organization: Could Perceptual Processes Be Affected?mentioning
confidence: 52%
“…Practices that are more variable lead to better learning than more repetitive practices. While variable practices result in more effective motor learning than constant practice, 4 random and serial variable practices are more effective than the blocked variable practice. 5,6 A point of convergence in all proposed behavioral hypotheses is that more variable practices demand more from mnemonic processes than more repetitive practices, being this feature responsible for the better learning observed in random and serial practices when compared with constant and blocked practices.…”
Section: Introductionmentioning
confidence: 94%
“…Peak velocity is a measure associated with the central control phase, that is, the preprogrammed phase of the action 9 . Random practice requires the reconstruction of the action plan with each new practice trial 20,21 . Bearing in mind that one of the task's goals is velocity, it is possible that this is the main parameter to be programmed during the trials.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was defined considering studies that used motor tasks similar to the one used in this study (Apolina´rio-Souza et al, 2016;Chiviacowsky & Wulf, 2002;Kaefer, Chiviacowsky, Meira, & Tani, 2014;Lage et al, 2007Lage et al, , 2017Meira, Fairbrother, & Perez, 2015). The mean sample size used in these studies was 12.5 participants.…”
Section: Participantsmentioning
confidence: 99%
“…The same dynamic strategy might be expected when a motor task requires learning more than one spatial or temporal goal. For example, sequential tasks can require both the learning of relative times between movement components (movement pattern) and the parallel learning of an absolute time (movement parameterization), characterized by the sum of each component time (Apolinário-Souza et al., 2016; Lage et al., 2017; Lai, Shea, Wulf, & Wright, 2000; Lelis-Torres, Ugrinowitsch, Apolinario-Souza, Benda, & Lage, 2017; Shea, Lai, Wright, Immink, & Black, 2001). In this type of motor task, the use of a dynamic information processing strategy is essential to learning.…”
Section: Introductionmentioning
confidence: 99%